Pengaruh Pelayanan Pengelola Terhadap Kepuasan Nasabah Bank Sampah - Aldy Wirawan; Pitri Yandri (UM. Bengkulu, 2023)
Waste banks are increasingly important to assist government programs in reducing household waste. The government has recognized the existence of waste banks as community-based waste management organizational entities through various laws and regulations. As an organization, waste banks must also adhere to sound management principles, including how to serve service users/customers (in this case, people who save their waste). However, research on waste banks focuses a lot on their role in the environment and how their members participate. Here, research related to management services functions is rarely carried out by researchers. Therefore, this study examines the effect of management services on the satisfaction of waste bank customers. We use the service and customer satisfaction theory and break it down into measurable indicators. This study looked at the Hibiscus Waste Bank in South Tangerang City. To answer the formulation of the problem, we surveyed more than 30 customers purposively through a questionnaire instrument. Then we examined it with the Structural Equation Modelling. We found strong evidence that physical evidence, responsiveness, empathy, assurance, and service reliability significantly affected waste bank customer satisfaction. Further elaboration of the findings we present more fully in this article.